THE CORRELATION AMONG STUDENTS’ LANGUAGE LEARNING ATTITUDE, STUDENTS’ MOTIVATION AND THEIR WRITING COMPETENCE AT SULTHAN THAHA SAIFUDDIN STATE ISLAMIC UNIVERSITY OF JAMBI - Susilawati; Zurnelli , Netti; Sumardi, Mayang Sastra (JR-ELT (Journal of Research in English Language Teaching), 2023)
The purposes of this research are to find out (1) correlation between students’ language learning attitude and their writing competence (2) correlation between students motivation and their writing competence (3) correlation among students’ language learning attitude, students motivation and their writing competence. The research design was correlation study. The subject of this reserach are the students of the fourth semester of English Education Study Program at Sulthan Thaha Saifuddin Jambi State Islamic University as the population. The total samples are 80 students. The data were collected by questionnaire and writing test. Next, the result of the coefficient correlation between students’ language learning attitude and their writing competence was r=0.604. it means that those variables are positive correlated. However, r=0.604 is considered high correlation. Then, the result of the coefficient correlation between students motivation and their writing competence was r=0.444. It means that those variables are positive correlated. however, r=0.444 is considered medium correlation. The last, correlation among students’ language learning attitude, students motivation and their writing competence was r=0.724. It means that those variables are positively correlated.